What’s in a Name? Symbolic Racism, Public Opinion, and the Controversy over the NFL’s Washington Football Team Name - Sharrow, Elizabeth A. (Race and social problems, 2021)
According to Daniel Snyder, owner of the National Football League Team formerly known as the Washington “Redskins,” “the name really means honor and respect.” For decades, Snyder pointed to polls that suggest majoritarian support among the American public to justify the continued use of the racially contested team moniker. However, Indigenous activists and their allies have long argued that the term “Redskins” is a racial slur. Using data from the 2014 Cooperative Congressional Election Study (CCES), this paper investigates the role of racial attitudes—specifically symbolic racism directed at Native Americans—in shaping public opinion about the name change during a period of heightened public attention to the debate over the team’s name. Our findings indicate that support for the continued use of the team’s name, though admittedly widespread among the American public, is in part influenced by negative racial attitudes directed at Native Americans. By engaging the literature on the politics of symbolic racism we demonstrate that, rather than “honoring” American Indians, those supportive of Native American mascots and symbols in professional football are significantly likely to begrudge them.